Zircon geochronology of basement granitoid gneisses and sedimentary rocks of the Tsodilo Hills Group in the Pan-African Damara Belt, western Botswana: age constraints, provenance, and tectonic significance. (November 2019) - Mapeo, R.B.M.; Wendorff, M.; Ramokate, L.V.; Armstrong, R.A.; Mphinyane, T.; Koobokile, M.
Abstract: New U–Pb sensitive high-resolution ion microprobe (SHRIMP) dating of zircon from granitoid gneisses and siliciclastic metasedimentary rocks of the Tsodilo Hills Group in the Pan-African Damara Belt in western Botswana were examined to determine the emplacement ages of the granitoids and to identify the provenance of the sediments and the source area. The sedimentary rocks nonconformably overlie granitoid gneisses. The U–Pb crystallisation ages of the cores in zircon grains in four samples from these gneisses are 2654.5 ± 5.3 to 2536.4 ± 5.8 Ma and 2199 ± 48 to 2049.6 ± 7 Ma, whereas the granitoids were emplaced between 2036 ± 3.8 and 1978 ± 23 Ma. The U–Pb SHRIMP zircon analysis of 247 detrital zircon grains from four samples of quartzite yielded 224 concordant to near-concordant zircon analyses defining five age groups of 3420.5 ± 7.9 to 3003.3 ± 7.7 Ma (n = 7), 2961 ± 13 to 2506 ± 11 Ma (n = 40), 2484 ± 15 to 2106 ± 7.7 Ma (n = 24), 2099 ± 11 to 2062 ± 26 Ma (n = 18), and 2057 ± 16 Ma to 1736 ± 200 Ma (n = 134). The results of petrography indicate that these are mature siliciclastic rocks. The presence of Palaeoarchean to Mesoarchean and Siderian to Orosirian detrital zircon grains in the sedimentary rocks, for which no likely source rocks occur in the region, suggests that the source rocks are unknown and were likely derived outside the immediate Archean Basement Complexes of South Central Africa. The complete absence of Mesoproterozoic (Calymmian) and younger detrital zircon grains in the Tsodilo Hills Group rocks, which could originate from the widespread nearby Calymmian to Tonian igneous complexes, suggests that the Tsodilo Hills Group metasedimentary rocks are older than the Damara Sequence of Botswana and Namibia. The Tsodilo Hills Group metasedimentary rocks are comparable in age to the Palaeoproterozoic to Mesoproterozoic metasedimentary rocks in eastern Zambia, southern Zambia, the Angola–Kasai Shield of southern Angola, the Eastern Domain of the Karagwe–Ankole Belt in the Congo–Tanzania Craton, and the Siderian to Orosirian sedimentary sequences in the São Francisco Craton of South America. Highlights: We report detrital zircon ages of the Tsodilo Hills Group exposed in the Damara Belt in western Botswana. The metasedimentary rocks are older than previously thought and were deposited during the Palaeoproterozoic period. Detritus was sourced from Archean and Palaeoproterozoic terranes including those in South Central Africa. The detrital age distribution shows similarities to the Palaeo- to Mesoproterozoic sequences in Congo and São Francisco cratons.